2008
DOI: 10.1021/bp049559j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sucrose and Maltodextrin on the Physical Properties and Survival of Air-Dried Lactobacillus bulgaricus: An in Situ Fourier Transform Infrared Spectroscopy Study

Abstract: The effect of sucrose, maltodextrin and skim milk on survival of L. bulgaricus after drying was studied. Survival could be improved from 0.01% for cells that were dried in the absence of protectants to 7.8% for cells dried in a mixture of sucrose and maltodextrin. Fourier transform infrared spectroscopy (FTIR) was used to study the effect of the protectants on the overall protein secondary structure and thermophysical properties of the dried cells. Sucrose, maltodextrin and skim milk were found to have minor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 21 publications
8
97
0
8
Order By: Relevance
“…Aside from proteins, there also exists a diverse range of applications to other (i.e. nonprotein) milk components, such as studies on the crystallinity of lactose in whey powder [29], determination of conjugated linoleic acids in cow's milk fat by FTRaman spectroscopy [25], or investigation of the effects of sucrose, maltodextrin and skim milk on survival of L. bulgaricus after drying [30].…”
Section: Other Applications New Techniques and Trends In Vibrationalmentioning
confidence: 99%
“…Aside from proteins, there also exists a diverse range of applications to other (i.e. nonprotein) milk components, such as studies on the crystallinity of lactose in whey powder [29], determination of conjugated linoleic acids in cow's milk fat by FTRaman spectroscopy [25], or investigation of the effects of sucrose, maltodextrin and skim milk on survival of L. bulgaricus after drying [30].…”
Section: Other Applications New Techniques and Trends In Vibrationalmentioning
confidence: 99%
“…Characterization of lactic acid bacteria (LAB) encapsulated with alginate using FTIR spectroscopy has been carried out by Le-Tien and others (34). The effect of drying and as well as of sugars on bacterial membrane structure and on secondary proteins has been studied by several other groups (26,40,45,46,47). Trehalose and sorbitol were effective in protecting cell envelopes and secondary proteins of probiotic bacteria during drying (33,40,45).…”
mentioning
confidence: 99%
“…3C). Sucrose, maltodextrin and monosodium glutamate are commonly used as protective compounds in the freeze-drying process [10]. Our results suggest that increasing the number of OH groups in the rehydration solution might make the membrane less permeable to electrolytes and could improve or maintain the viability, possibly by protecting membrane phospholipids.…”
Section: Resultsmentioning
confidence: 80%
“…These results accord with those reported by other authors, who have shown that the direct interaction between sucrose and membrane might contribute to the protective effects of sucrose on the dried cells of Lb. Bulgaricus [10]. These authors suggested that OH groups of sugar and/or polyalcohol could replace water and could interact with phospholipids to maintain membrane integrity.…”
Section: Resultsmentioning
confidence: 99%